Studying Shakespeare in performance - Brown, John Russell (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2011)
"John Russell Brown is arguably the most influential scholar in the field of Shakespeare in performance. This collection brings together, and makes accessible, his most important writing across the last 40 years. Together these essays provide an authoritative and engaging account of how to study Shakespeare's plays as texts for performance"--
Machine generated contents note: -- Acknowledgments -- Introduction -- PART I: STUDY -- Theatre Criticism and Literary Criticism -- Research in the Service of Theatre -- Writing about Shakespeare's Plays in Performance -- PART II: WORDS AND ACTIONS -- The Nature of Speech in the Plays -- Acting in the Plays -- Shakespeare's Subtext -- Shakespeare's Use of Space -- PART III: PRODUCTIONS -- Free Shakespeare -- Representing Sexuality -- Violence and Sensationalism -- PART IV: DIRECTORS -- Franco Zeffirelli's Romeo and Juliet -- Three Directors -- PART V: AUDIENCES -- Play-going and Participation -- Asian Theatres and European Shakespeares -- Index.
Includes bibliographical references and index.
Purchased from DSB Enterprise, Bill No.217
Keywords: Shakespeare, William, -- 1564-1616 -- Dramatic production; Shakespeare, William, -- 1564-1616 -- Stage history; LITERARY CRITICISM / Shakespeare; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; PERFORMING ARTS / Theater / History & Criticism